The Minnesota Code Manual of Electrocardiographic Findings - Prineas, Ronald J.; Crow, Richard S.; Zhang, Zhu-Ming.; SpringerLink (Online service) (London : Springer London, 2010)
The electrocardiogram (ECG) is most often used in clinical and hospital settings for diagnosis and prognosis, but it is also used for systematic population studies and clinical trials where a repeatable, valid, and quantitative method is required for classification of ECG findings related to disease. Useful classification depends, in turn, on standardized methods of acquiring the data, on mounting (sampling), and on efficient and effective reading and measurement of the ECG. This new edition of the classic reference Minnesota Manual of Electrocardiographic Findings has been prompted by the continuous refinements and extensions to the Minnesota Code that allow a greater range of abnormalities to be coded; there are even clearer means of demonstrating correct and standardized methods of measurements, which are incorporated into this extensively revised second edition; some minor coding rules have been changed; and now the use of the code has been greatly expanded and is used in countless epidemiologic studies and clinical trials worldwide. While the contents of the coding chapters of this manual need not be mastered in one reading, the manual should be used as a reference when there is doubt about how to measure a particular wave form. The manual should be an important addition to the libraries of electrocardiographers, all clinical trialists and experienced investigators to teach measurement and coding of ECGs. The information contained within these pages is also key reading for all trainee physicians in internal medicine and cardiology, and nurses, technicians and other professionals involved in the management of patients needing ECG evaluation.
Preface for the second edition -- Preface for the first edition -- Acknowledgments -- 1 What is the Electrocardiogram or ECG? The Electricity Part of the ECG -- 2 ECG Leads Bipolar Limb Leads (I, II, III) / Unipolar Limb Leads (aVR, aVL, aVF) / Chest Leads (V1, V2, V3, V4, V5, V6) -- 3 Measuring Devices Recording Paper Grid / Measuring Loupe / Plastic Ruler / Calibration Deflection / Beats to Be Measured / Mathematical Symbols -- 4 Q-QS Waves (1-Codes) -- 5 Frontal Plane QRS Axis (2-Codes) -- 6 High R-Waves (3-Codes) -- 7 ST Segment Depression (4-Codes) and Negative T-Waves (5-Codes) -- 8 Atrioventricular (A-V) Conduction Defects (6-Codes) -- 9 Intraventricular Conduction Defects (7-Codes) -- 10 Arrhythmias (8-Codes) -- 11 Miscellaneous Codes (9-Codes) -- 12 Exact Measurements Frontal Plane QRS Axis / Amplitude Measurements / Q-X, Q-T Intervals -- 13 Coding the Whole ECG Coding Hierarchy / Data Recording -- 14 ECG Data Acquisition Procedures and Maintenance of Recording Quality including Technician Training Twelve-Lead Rest ECG Using Single Channel Recorder / Twelve-Lead ECG Using Multichannel Recorder / Minimizing Biologic Variability -- 15 Criteria for Significant ECG Pattern Change -- 16 ECG Indices That Add to Independent Prognostication for Cardiovascular Disease Outcomes -- 17 Quality Control of Visual and Electronic Coding -- Appendix I Minnesota Code 2009 Q and QS Patterns / QRS Axis Deviation / High Amplitude R-Waves / ST Junction (J) and Segment Depression / T-Wave Items / A-V Conduction Defect / Ventricular Conduction Defect / Arrhythmias / ST Segment Elevation / Miscellaneous Items / Incompatible Codes -- Appendix II Novacode and Minnesota Code Equivalents -- Appendix III Major and Minor ECG Abnormalities for Population Comparisons with Minnesota Code and Novacode Equivalents.
Keywords: Medicine; Emergency medicine; Internal medicine; Cardiology; Medicine & Public Health; Cardiology; Emergency Medicine; Internal Medicine